2017
DOI: 10.1186/s40560-017-0263-7
|View full text |Cite
|
Sign up to set email alerts
|

Contribution to diagnosis and treatment of bone marrow aspirate results in critically ill patients undergoing bone marrow aspiration: a retrospective study of 193 consecutive patients

Abstract: BackgroundThe purpose of the work was to assess the contribution to diagnosis and/or treatment (CDT) of bone marrow aspiration (BMA) in the critically ill patient.MethodsThe retrospective study included 193 patients. On the basis of BMA findings, contribution to diagnosis was defined by one of four previously unestablished diagnoses (maturation arrest of granulocyte precursors, hemophagocytic lymphohistiocytosis, hematological malignancy, marrow infiltration with cancer cells) and to treatment as the initiatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Persistent fever that is refractory to antibiotics, pancytopenia, major hyperferritinemia, or unexplained liver enzyme elevation should lead practitioners to screen patients for HLH (35)(36)(37). Although variable and non-specific, bonemarrow hemophagocytosis is still a hallmark HLH criterion (38)(39)(40) and was associated with a higher ICU mortality rate in our study. Among biological factors, non-regenerative profound anemia and hypofibrinogenemia have been reported to be independent predictors of a poor outcome (31)(32)(33)41).…”
Section: Discussionmentioning
confidence: 57%
“…Persistent fever that is refractory to antibiotics, pancytopenia, major hyperferritinemia, or unexplained liver enzyme elevation should lead practitioners to screen patients for HLH (35)(36)(37). Although variable and non-specific, bonemarrow hemophagocytosis is still a hallmark HLH criterion (38)(39)(40) and was associated with a higher ICU mortality rate in our study. Among biological factors, non-regenerative profound anemia and hypofibrinogenemia have been reported to be independent predictors of a poor outcome (31)(32)(33)41).…”
Section: Discussionmentioning
confidence: 57%
“…Persistent fever that is refractory to antibiotics, pancytopenia, major hyperferritinemia, or unexplained chemical hepatitis should lead practitioners to screen patients for HLH [31][32][33]. Although variable and non-speci c, bone-marrow hemophagocytosis is still a hallmark HLH criterion [34][35][36] and was associated with a higher ICU mortality rate in our study. Among biological factors, non regenerative profound anemia and hypo brinogenemia have been reported to be independent predictors of a poor outcome [27][28][29]37].…”
Section: Discussionmentioning
confidence: 58%
“…As a result, the authors concluded that BMA could significantly contribute to diagnosis and treatment in patients with or without any hematological malignancy during admission to the intensive care unit. 7 In our study, the BMA evaluation directly contributed to the diagnosis and treatment of 200 (40%) patients, including 186 (37.2%) with malignant hematological diseases and 14 (2.8%) with benign hematological diseases. In a study by Gilotara et al in 100 cases, when the results of BMA and BMB assessment were compared, there was a 72.4% agreement.…”
Section: A H E a D O F P R I N Tmentioning
confidence: 78%